Systematic Review of the Effects of Chemical Insecticides on Four Common Butterfly Families - Mulé, Rosaria; Sabella, Giorgio; Robba, Lavinia; Manachini, Barbara (Frontiers in Environmental Science, 2017)
Safeguarding crop productivity by protecting crops from pest attacks entails the wide use of plant protection products that provide a quick, easy and cheap solution. The objective of this study is to understand the effects of insecticides used in agriculture on non-target butterflies, specifically on the families Lycaenidae, Nymphalidae, Hesperiidae and Papilionidae. To achieve this goal, a formal systematic review was performed according to European Food Safety Authority (EFSA) guidelines, by entering a combination of keywords on 3 online databases. Three reviewers independently extracted information on study characteristics and quality. The main results were collected and grouped by the insecticide used, butterflies species and family, and endpoints. The output was valuable but heterogeneous as the endpoints and methodologies of the studies reviewed were different. Few experimental studies on the effects of insecticides on the most common butterfly families have been published. Naled and permethrin are the most commonly used insecticides in the experiments, whilst the target organisms of these studies are Vanessa cardui, Danaus plexippus, Heliconius charitonius, belonging to the Nymphalidae family, and Eumaeus atala, belonging to the Lycaenidae family; the effects were evaluated on all developmental stages, with special attention to the larval phase. This systematic review highlights the need for more studies on the effects of chemical insecticides on non-target Lepidoptera in light of their ecological importance and the extensive use of these chemical products.